ANALYZING THE FINANCIAL EFFICIENCY AND STABILITY OF FMCG COMPANIES IN INDONESIA: A STUDY OF INVENTORY TURNOVER AND DEBT-TO-EQUITY RATIOS - Haura Nasywa, Fediola
Fast Moving Consumer Goods (FMCG) companies ideally should have a high inventory turnover rate (ITR) due to its rapid shelf turnover; they produce fast and are sold fast since the demand is high. Inventory turnovers are one of the most important considerations for retailers, as nearly every retailer has an inventory management strategy in place. They have to be able to control their inventory as it indicates how quickly the company sells and how often it replenishes their inventory. Too much inventory and lesser sales, could result in spending a lot of capital on maintaining inventory or overstocking poorly selling products understocking can result in missed sales opportunities. Company’s solvability depends on how liquid is the company and how well they could pay off its debt; this also relates to how they finance their company which is where the calculation of debt-to-equity (D/E) ratio is useful. This determines whether the company uses equity to finance their operations or instead rely on debt to finance their operational expenses. As the research began with a preliminary analysis, after obtaining the list of 87 listed FMCG companies from Indonesian Stock Exchange and their current ratio numbers from Stockbit, 64.37% of companies’ ITR in Indonesia are way below the current average ratio which was 3.31. This research will be designed qualitatively by using the quantitative numbers given from companies publicly posted financial statements and annual reports with complementary knowledge from secondary data derived from the company's website and other resources including reputable journals, mass media, and online articles. Lenders will be more likely to lend more money when indeed to the companies who have lower D/E ratio compared to other companies with higher D/E. A high ITR and low D/E can make a company more agile, reduce the burden of interest payments, which eventually will make it easier for the company to invest in profitable opportunities, and lead to higher ROA.